Autonomic dysfunction is associated with neuropsychological impairment in Lewy body disease - Pino, Rocío Del; Murueta-Goyena, Ane; Acera, Marian; Carmona-Abellan, Mar; Tijero, Beatriz; Lucas-Jiménez, Olaia; Ojeda, Natalia; Ibarretxe-Bilbao, Naroa; Peña, Javier; Gabilondo, Iñigo; Gómez-Esteban, Juan Carlos (Journal of Neurology, 2020)
Objective: This study aimed to analyze the association of autonomic dysfunction with cognition, depression, apathy, and fatigue in Lewy body disease (LBD). Methods: We included 61 patients [49 with idiopathic Parkinson’s disease, 7 with dementia with Lewy bodies, and 5 E46K-SNCA mutation carriers] and 22 healthy controls. All participants underwent a comprehensive battery of neuropsychological and clinical measures, autonomic symptom assessment with the SCOPA-AUT, analysis of non-invasive hemodynamic parameters during deep breathing, the Valsalva maneuver, and a 20-min tilt test, and electrochemical skin conductance measurement at rest (Sudoscan). Student’s t tests were used to assess group differences, and bivariate correlations and stepwise linear regressions to explore associations between autonomic function, cognition, depression, apathy, and fatigue. Results: Compared to controls, patients who had significant impairment (p < 0.05) in cognition, higher depression, apathy, and fatigue, more autonomic symptoms and objective autonomic dysfunction, reduced deep breathing heart rate variability [expiratory-to-inspiratory (E/I) ratio], prolonged pressure recovery time, and lower blood pressure in Valsalva late phase II and phase IV, while 24.1% had orthostatic hypotension in the tilt test. Autonomic parameters significantly correlated with cognitive and neuropsychiatric outcomes, systolic blood pressure during the Valsalva maneuver predicting apathy and depression. The E/I ratio was the main predictor of cognitive performance (17.6% for verbal fluency to 32.8% for visual memory). Conclusion: Cardiovascular autonomic dysfunction is associated with cognitive and neuropsychiatric impairment in LBD, heart rate variability during deep breathing and systolic blood pressure changes during the Valsalva procedure are the main predictors of neuropsychological performance and depression/apathy symptoms, respectively.
Keywords: apathy; autonomic dysfunction; cognition; depression; lewy body disease; parkinson disease; Scopus; JCR